2017
DOI: 10.1038/srep40328
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age and vaccination history on long-term serological responses after symptomatic B. pertussis infection, a high dimensional data analysis

Abstract: Capturing the complexity and waning patterns of co-occurring immunoglobulin (Ig) responses after clinical B. pertussis infection may help understand how the human host gradually loses protection against whooping cough. We applied bi-exponential modelling to characterise and compare B. pertussis specific serological dynamics in a comprehensive database of IgG, IgG subclass and IgA responses to Ptx, FHA, Prn, Fim2/3 and OMV antigens of (ex-) symptomatic pertussis cases across all age groups. The decay model reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…The rising percentage of pertussis cases in Japanese teenagers or adults [ 84 ] suggests waning immunity to be one contributing factor, coupled with a vaccination schedule that incorporates a booster at an early age (2 years) but lacks a secondary immunization for adolescents, as championed in the USA [ 2 ]. Recent studies revealed that the level of decrease in vaccine effectiveness against pertussis disease depends on both the specific vaccine antigen and the subject’s age [ 85 ]. As a short-term solution, the efficacy of existing vaccines may be improved by a change in vaccination booster regimens, by an expansion of maternal immunizations or by improving existing ACV antigens.…”
Section: Resultsmentioning
confidence: 99%
“…The rising percentage of pertussis cases in Japanese teenagers or adults [ 84 ] suggests waning immunity to be one contributing factor, coupled with a vaccination schedule that incorporates a booster at an early age (2 years) but lacks a secondary immunization for adolescents, as championed in the USA [ 2 ]. Recent studies revealed that the level of decrease in vaccine effectiveness against pertussis disease depends on both the specific vaccine antigen and the subject’s age [ 85 ]. As a short-term solution, the efficacy of existing vaccines may be improved by a change in vaccination booster regimens, by an expansion of maternal immunizations or by improving existing ACV antigens.…”
Section: Resultsmentioning
confidence: 99%
“…This is underlined by the fact that the majority of our participants showed pre-booster PT-IgA levels, that further increased post-booster. IgA responses are not induced by aP vaccines in infants ( 22 ), but exposure to B. pertussis induces systemic pertussis-specific IgA-producing memory B-cells in children and adults ( 22 , 33 ). Therefore, the presence of IgA antibodies pre-booster and their rise post-booster may result from the activation of pre-existing pertussis-specific memory B-cells induced by previous B. pertussis contact in life, indicative of enhanced B. pertussis circulation nowadays.…”
Section: Discussionmentioning
confidence: 99%
“…This was likely due to the unspecific binding of the protein-A label to the IgA and IgM antibodies from the samples, as a test with anti-human IgG label conjugate (Figure 3) produced no signal with the same samples from the PT test line. (16,17), (g) both PRN and FHA positive, (18,19), and (h) all negative samples (1,2,3). Please refer to Table 1 for antibody concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the simultaneous measurement of IgA, IgG and IgM antibody levels has been reported to provide the most diagnostic accuracy [27], especially if interpreted in connection with clinical findings [28], but may also lead to overdiagnosis [14,29]. Considering IgG subclasses, IgG1 and 4 responses were elevated to multiple antigens in children primed with acellular pertussis vaccines [17,[30][31][32], whereas, in patients or unvaccinated convalescent children, IgG1 and IgG3 were more prevalent [30,31,33]. Therefore, the multiplexing of IgG1, 3 and 4 could provide a more comprehensive image to separate recent vaccination and infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation